2022
DOI: 10.1155/2022/9993743
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Humulus japonicus Extract and Polysaccharide-Rich Extract of Phragmites rhizoma in Rats with Gastrointestinal Dysfunctions Induced by Water Avoidance Stress

Abstract: Chronic stress can cause the gastrointestinal disorders characterized by an altered bowel movement and abdominal pain. Studies have shown that Humulus japonicus extract (HJE) has anti-inflammatory and antidiarrheal effects, and Phragmites rhizoma extract (PEP) has antioxidative and antistress effects. The present study aimed to investigate the possible effects of HJE and PEP in rat models with stress-induced gastrointestinal dysfunctions. The rats were exposed to water avoidance stress (WAS, 1 h/day) for 10 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Here, the protein levels of Occludin, and Claudin1 in the colon were significantly decreased in rats with WAS compared to those in the control group, suggesting that WAS affected mucosal barrier integrity and led to intestinal barrier dysfunction. These results are consistent with previous reports that psychological stress generally increases intestinal permeability, regardless of the type of stress, such as communication box-induced stress or restraint stress [ 42 , 43 ]. PCNA is an intranuclear protein that assists DNase.…”
Section: Discussionsupporting
confidence: 93%
“…Here, the protein levels of Occludin, and Claudin1 in the colon were significantly decreased in rats with WAS compared to those in the control group, suggesting that WAS affected mucosal barrier integrity and led to intestinal barrier dysfunction. These results are consistent with previous reports that psychological stress generally increases intestinal permeability, regardless of the type of stress, such as communication box-induced stress or restraint stress [ 42 , 43 ]. PCNA is an intranuclear protein that assists DNase.…”
Section: Discussionsupporting
confidence: 93%
“…Injured mice treated with squid ink polysaccharide (OBP) exhibit significantly enhanced mRNA expression of occludin, ZO-1 and ZO-2 tight junction proteins after immunohistochemical staining; 99 Astragalus polysaccharide (APS) also exhibits significantly elevated jejunal ZO-1 and claudin-1 protein expression; 100 Humulus japonicus extract (HJE) increases TJs in the colon. 113 These experiments corroborate that natural polysaccharides can upregulate the expression of tight junction proteins, reverse the increased intestinal permeability brought about by disease, and protect the integrity of the intestinal barrier.…”
Section: The Mechanism Of Action Of Natural Polysaccharides In the Tr...mentioning
confidence: 57%
“…Hao et al (2022) demonstrated that feeding weaned piglets with 2% HS‐containing diet increased the abundance of Lactobacillus, Ruminococcaceae, Enterococcus and Pseudomonas in cecum content. Thein et al (2022) investigated the effects of HS extract‐containing additives in stress‐induced gastrointestinal dysfunctions rat models. They observed that the supplementation of additive alleviated the increase of colonic permeability and the concentration of intestinal tumour necrosis factor‐α and thiobarbituric acid reactive substances, as well as the reduction of intestinal claudin‐1 and occludin expressions induced by stress.…”
Section: Application Of Hs and Its Productsmentioning
confidence: 99%